PENGARUH GAIN TERHADAP FWHM DAN FWTM PADA CITRA B-MODE ULTRASONOGRAM (USG) - Amitasari, Ria; Suryono, Suryono; Adi, Kusworo (BERKALA FISIKA, 2015)
The effect of gain to The Width at Half Maximum (FWHM) and Full Width at Tenth Maximum (FWTM) on B-mode image ultrasonogram (USG) has been investigated. The aim of this research is to determine the effect of gain on the spatial resolution according the measurements of FWHM and FWTM. The evaluated resolution type is axial and lateral. This research used phantom multipurpose multi tissue with gain (30 dB, 35 dB, 40 dB, 45 dB, 50 dB, 55 dB and 60 dB) on frequency variation source 6,2 Mhz, 8 MHz dan 10MHz. The axial and lateral resolution images were obtained by using USG which uses B-Mode imaging. The measurement was made by using digital image and calculated objectively with MATLAB. The measurement of FWHM and FWTM was obtained from IP-PSF analysis (In Plane-Point Spread Function) using approximation for the Gaussian function. The result shows that there is influence from gain on FWHM and FWTM. The decreasing gain resulted in decreasing of FWHM and FWTM. The decreasing of FWHM and FWTM represents better spatial resolution, and vice versa. Keywords: FWHM, Gain, Point Spread Function, Spatial resolution, USG,